Kesetaraan Gender dalam Mencapai Pendidikan Inklusif - Nengyanti, Nengyanti; Saptawan, Ardiyan Saptawan; Imania, Katriza Imania; Permatasari, Indah; Wulandari, Putri Uzdah; Adventy, Maria Immaculata Yovita; Izzudin, Muhammad; Yanti, Mery (Universitas Negeri Surabaya, 2025)
Gender inequality in education remains a persistent issue, with boys and girls often facing different expectations, opportunities, and treatment within learning environments.This research focuses on gender equality between girls and boys in the context of inclusive education, aiming to identify empowerment patterns that address barriers to educational access. Using quantitative methods, data were collected through questionnaires completed by students at the elementary and junior high school levels. Analysis was conducted to understand the challenges of gender disparities in educational participation. The results indicate significant differences in participation between male and female students, with boys dominating in high-intensity physical sports and girls more engaged in the arts. Additionally, there were differences in teachers' attitudes towards students based on gender. This study aims to create empowerment strategies and more inclusive education policies, providing guidance for policymakers and educational practitioners to support gender equality in the education sector.